Massive hard palate tumor removed with an electric knife - Ratajek-Gruda, Monika; Osica, Piotr; Janas-Naze, Anna (Journal of Education, Health and Sport, 2017)
The article describes a case of a 70-year-old patient with a massive hard palate tumor removed with an electric knife.